2020
DOI: 10.1016/j.jval.2020.04.994
|View full text |Cite
|
Sign up to set email alerts
|

Pnd103 Productivity Loss Among Non-Elderly Adults With Multiple Sclerosis in the United States: A Propensity Score Matched Study

Abstract: Objectives: MG is a debilitating chronic illness characterized by muscle weakness, potentially life-threatening exacerbations and high costs. We sought to further quantify the humanistic and economic burden by reviewing published evidence. Methods: Using PRISMA guidelines, two systematic literature reviews were conducted, one for quality of life (QOL) and one for economic studies, in key biomedical literature databases, Embase, Ovid Medline and Cochrane. Additionally, only studies published between 2009-2019 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…11 A propensity score-matched study using Medical Expenditure Panel Survey (2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015) data found that significantly greater proportions of patients with MS had arthritis (42.1% vs 30.1%), depression (29.7% vs 13.3%), anxiety (17.1% vs 8.5%), osteoporosis (5.7% vs 2.4%), and anemia (5.5% vs 1.8%), compared with controls (all P < .05). 12 Approximately 25% to 30% of US patients with MS are Medicare beneficiaries; however, limited information exists on this population. 13 Previous studies have documented the high costs borne by traditional Medicare patients with MS, and large proportions of the costs were associated with comorbidity.…”
Section: Journal Of Health Economics and Outcomes Researchmentioning
confidence: 99%
“…11 A propensity score-matched study using Medical Expenditure Panel Survey (2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015) data found that significantly greater proportions of patients with MS had arthritis (42.1% vs 30.1%), depression (29.7% vs 13.3%), anxiety (17.1% vs 8.5%), osteoporosis (5.7% vs 2.4%), and anemia (5.5% vs 1.8%), compared with controls (all P < .05). 12 Approximately 25% to 30% of US patients with MS are Medicare beneficiaries; however, limited information exists on this population. 13 Previous studies have documented the high costs borne by traditional Medicare patients with MS, and large proportions of the costs were associated with comorbidity.…”
Section: Journal Of Health Economics and Outcomes Researchmentioning
confidence: 99%
“…11 A propensity score-matched study using Medical Expenditure Panel Survey (2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015) data found that significantly greater proportions of patients with MS had arthritis (42.1% vs 30.1%), depression (29.7% vs 13.3%), anxiety (17.1% vs 8.5%), osteoporosis (5.7% vs 2.4%), and anemia (5.5% vs 1.8%), compared with controls (all P < .05). 12 Approximately 25% to 30% of US patients with MS are Medicare beneficiaries; however, limited information exists on this population. 13 Previous studies have documented the high costs borne by traditional Medicare patients with MS, and large proportions of the costs were associated with comorbidity.…”
Section: Journal Of Health Economics and Outcomes Researchmentioning
confidence: 99%